Sertão e sertanejos: antinomias narradas entre o pensado no Brasil e o vivido no norte de Minas Gerais - Oliveira Filho, Otaviano de (2018)
This thesis tries to contrast the categories "sertão" and "sertanejo" from the contents constructed between the Brazilian social thought and the experiences of northern miners. Starting from the assumption that these categories constitute a complex semantic ballast that evidences a historical-social matter crossed by diverse places of enunciation, I propose the confrontation of this theme from its narrative envelope, considering it as also resulting from a discursive construction which is a significant, strategic part of the narratives of the Brazilian nation that took shape precisely at the end of the eighteenth century. The delimitation of a territory - the northern sertão of Minas Gerais - and the consequent classification of its inhabitant - the sertanejo - occurs here from the rationalization of a range of verbal texts accessed during the research process in one part and another of the enunciation on the sertão and the sertão that builds Brazil or lived locally. If, on the one hand, these categories are structuring of Brazilian social thought and apprehensible in its contents in reports of European travelers, historiographical, memorialistic and academic texts, chronicles, essays, popular songs, etc., on the other hand, I consider that the northern miners disseminate content that, at times, replicates the thought and also the constructed interpretations having lived as the foundation to think the world in which they live. The sertaneja narrative, in its various formats and supports, which has been a recurrent source of systematic research in the last four decades, is taken here from a relational perspective, as a counterpart of the historical experience experienced by the living in their communities dispersed by the great call backwoods